ANALISIS KEMAMPUAN PEMECAHAN MASALAH PADA MODEL PROBLEM BASED LEARNING DISERTAI REMEDIAL TEACHING - samsul arifin; Kartono kartono; Isti Hidayah (EduMa: Mathematics education learning and teaching, 2019)
The purpose of this research are (1) to analyze the learning quality of problem based learning model which is accompanied by gave remedial teaching, (2) to described remedial teaching process a follow up diagnostic assessment, and (3) to analyze the ability of solving mathematical problems students are reviewed from cognitive style. This research is a mixed method research of concurrent embedded types. The research population were students of class XI MIPA SMA 1 Bojong Tegal. The result of mathematical problem solving ability test was analyzed qualitatively using mean test, comprehensive test, mean deviation test, and deviation proportion test Result of this research shows learning quality of PBL learning model with remedial teaching is considered well both qualitatively and quantitatively. The provision of diagnostic tests and remedial teaching treatment is effective to improve problem solving abilities, and the problem solving ability of independent field students is better than field dependent students.